Choosing initial MS therapy; personal, disease, and medication factors - Bruce A. Cohen (Neurotherapeutics)
Initiating disease modifying therapy in a patient with newly diagnosed relapsing multiple sclerosis currently offers the best opportunity to influence their subsequent disease course. This article reviews personal factors, disease presentation characteristics, and data on current disease modifying therapies from the perspective of choosing initial treatment in this setting. Although metrics for prognostication at the individual level remain unreliable, particularly for those with mild presentations, currently available data on the relative efficacy of disease modifying therapies supports offering high efficacy therapy first line to most patients with newly diagnosed relapsing multiple sclerosis.